(untitled) (Third Sector Social Economic Review, 2024)
The ability of a country to increase its income, employment level and quality of life is expressed by the concept of competitiveness. This concept also involves the ability to balance international trade, exports and foreign trade. Within this broad definition, Porter (1990) suggests that the concept of competitiveness should be considered in a wide range of international competition, taking into account market segments, differentiated products, technology differences and economies of scale. In this context, competitiveness at the micro level (firm, industry) is determined by how the economic value created by the sector is divided, how much is in the hands of the companies in the sector, how much is reserved for bargaining with customers and suppliers, limited by substitutes or captured by potential new entrepreneurs. The study aims to examine the impact levels of Porter’s five competitive forces which are (1) customers, (2) substitute products, (3) new ventures, (4) suppliers and (5) inter-firm competition on the competitiveness of the manufacturing industry in Çorum. According to the analyses, it is concluded that there is a positive relationship between the factors in Porter’s 5 forces model and the competitiveness of the companies operating in the manufacturing industry in Çorum. According to the results, Factor 1: Intra-firm competition α=0.835, Factor 2: New entrants α=0.762, Factor 3: Customers α=0.834, Factor 4: Substitutes α=0.677 and Factor 5: Suppliers α=0.765 have an effect on the competitiveness of the manufacturing industry in Çorum.